2021
DOI: 10.1155/2021/5512524
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 as a Biomarker and the Outcome of Its Inhibitors in the Clinical Trial: The Therapy Opportunity in Tumor

Abstract: Tumors are the foremost cause of death worldwide. As a result of that, there has been a significant enhancement in the investigation, treatment methods, and good maintenance practices on cancer. However, the sensitivity and specificity of a lot of tumor biomarkers are not adequate. Hence, it is of inordinate significance to ascertain novel biomarkers to forecast the prognosis and therapy targets for tumors. This review characterized LSD1 as a biomarker in different tumors. LSD1 inhibitors in clinical trials we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 93 publications
(119 reference statements)
0
13
0
Order By: Relevance
“…Some of these drugs have entered clinical studies for tumor malignancies, including ORY-1001, CC-90011, INCB059872, TCP, GSK-2879552, IMG-7289, and ORY-2001. 5 Thrombocytopenia has been considered the most prevalent treatment-related adverse event with LSD1 inhibitors in clinical studies. The study by Johnston et al 81 attributed this toxicity to megakaryocytic stem cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these drugs have entered clinical studies for tumor malignancies, including ORY-1001, CC-90011, INCB059872, TCP, GSK-2879552, IMG-7289, and ORY-2001. 5 Thrombocytopenia has been considered the most prevalent treatment-related adverse event with LSD1 inhibitors in clinical studies. The study by Johnston et al 81 attributed this toxicity to megakaryocytic stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…Lysine-specific demethylase 1 is a monoamine oxidase homolog, which precisely removes methyl groups of H3K4/H3K9, thus triggering activation or suppression of genes. 3 - 5 Lysine-specific demethylase 1 control of gene expression has been revealed to be vital to manifold procedures together with organogenesis and stem cell differentiation. 6 , 7 Lysine-specific demethylase 1 plays a key role in non-histone proteins by getting rid of mono- and di-methylation which could be linked to tumor progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of LSD1 biochemistry in physiological and pathological states have revealed that it is an orchestra protein, significantly involved in the regulation of cellular metabolism, based on its methyl group eraser activity and broad substrate specificity, which includes histone proteins (H3K4/9me) but also DNMT1, p53, STAT3, and E2F1, all of which play an important role in controlling the gene expression machinery [31]. The demethylase plays a particular role in cancer medicine as overexpression of LSD1 has been found in many types of cancer [18,32,33]. In consequence of detailed studies and identified effects on e.g.…”
Section: Discussionmentioning
confidence: 99%
“…13,[17][18][19][20][21][22][23] Consequently, various irreversible LSD1 inhibitors have been developed in recent years, with some currently undergoing clinical trials for AML. [24][25][26][27] To further enhance the anti-leukemic effects of existing treatments, various drug combinations containing LSD1 inhibitors have been studied to date, and shown synergy in the induction of differentiation and cytotoxicity, e.g. in combination with azacitidine, retinoic acid, mTOR or BET inhibitors.…”
Section: Introductionmentioning
confidence: 99%